Aplikasi Pupuk SP-36 dan Pupuk Kandang Sapi terhadap Ketersediaan dan Serapan Fosfor pada Tanah Inceptisol Kwala Bekala - Rino Lindri Chuaca; MMB Damanik; Posma Marbun (Universitas Sumatera Utara, 2017)
The objective of this study is to determine the effect of SP-36 fertilizer application and cow manure on the availability and P uptake on Inceptisol taken from Kwala Bekala. This research conducted in gauze house, Soil Fertility Chemical Laboratory, Faculty of Agriculture, University of North Sumatra and PT. Nusa Pusaka Kencana & QC Analytical Laboratory (Asian Agri Group). This study used Randomized Block Design which consist of two factors with three replications Factor I: SP-36 fertilizer (P) with 4 levels dose (ppm / 10 kg BTKO) ie: P0 (0), P1 (100), P2 (200), P3 (300) and factor II: cow manure (S) with 4 levels dose (g / 10 kg BTKO), namely: S0 (0), S1 (50), S2 (100) and S3 (150). The results showed that SP-36 fertilizer application significantly increased soil available P and P-plant uptake. Cow manure significantly increased P-plant uptake. The interaction between SP-36 fertilizer and cow manure significantly increased P-plant uptake. The best treatment was the application 300 ppm P2O5 SP-36 and cow manure 20 tons/ha